Production and analysis of a mammalian septin hetero‐octamer complex - DeRose, Barry T.; Kelley, Robert S.; Ravi, Roshni; Kokona, Bashkim; Beld, Joris; Spiliotis, Elias T.; Padrick, Shae B. (Cytoskeleton (Hoboken, N.J.), 2020)
The septins are filament‐forming proteins found in diverse eukaryotes from fungi to vertebrates, with roles in cytokinesis, shaping of membranes and modifying cytoskeletal organization. These GTPases assemble into rod‐shaped soluble hetero‐hexamers and hetero‐octamers in mammals, which polymerize into filaments and higher order structures. While the cell biology and pathobiology of septins are advancing rapidly, mechanistic study of the mammalian septins is limited by a lack of recombinant hetero‐octamer materials. We describe here the production and characterization of a recombinant mammalian septin hetero‐octamer of defined stoichiometry, the SEPT2/SEPT6/SEPT7/SEPT3 complex. Using a fluorescent protein fusion to the complex, we observed filaments assembled from this complex. In addition, we used this novel tool to resolve recent questions regarding the organization of the soluble septin complex. Biochemical characterization of a SEPT3 truncation that disrupts SEPT3‐SEPT3 interactions is consistent with SEPT3 occupying a central position in the complex while the SEPT2 subunits are at the ends of the rod‐shaped octameric complexes. Consistent with SEPT2 being on the complex ends, we find that our purified SEPT2/SEPT6/SEPT7/SEPT3 hetero‐octamer copolymerizes into mixed filaments with separately purified SEPT2/SEPT6/SEPT7 hetero‐hexamer. We expect this new recombinant production approach to lay essential groundwork for future studies into mammalian septin mechanism and function.